A randomized trial to assess the potential of different beverages to affect hydration status: development of a beverage hydration index ? - Maughan, R. J.; Watson, P.; Cordery, P.; Walsh, N. P.; Oliver, S. J.; Dolci, A.; Rodriguez-Sanchez, N.; Galloway, S. D. R. (The American Journal of Clinical Nutrition, 2016)
Background: The identification of beverages that promote longer-term fluid retention and maintenance of fluid balance is of real clinical and practical benefit in situations in which free access to fluids is limited or when frequent breaks for urination are not desirable. The postingestion diuretic response is likely to be influenced by several beverage characteristics, including the volume ingested, energy density, electrolyte content, and the presence of diuretic agents.